2023
DOI: 10.1186/s12871-023-02078-0
|View full text |Cite
|
Sign up to set email alerts
|

Penehyclidine hydrochloride for treating postoperative nausea and vomiting after laparoscopic bariatric surgery: a double-blinded randomized controlled trial

Abstract: Background Postoperative nausea and vomiting (PONV) is a common and distressing complication of laparoscopic bariatric surgery (LBS). Penehyclidine hydrochloride has been reported to be effective in preventing PONV. Considering the potential preventive effects of penehyclidine against PONV, we hypothesized that intravenous infusion of penehyclidine may alleviate PONV within the first 48 h in patients scheduled for LBS. Methods Patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…13,14 Previous studies have shown that the mechanism of penehyclidine reducing the incidence of PONV is complex, which may be related to its blocking of the muscarinic acetylcholine receptor, which is involved in the development of PONV through various mechanisms. Recent clinical studies have shown that penehyclidine for prevention of PONV has made good progress in some surgical procedures, such as ophthalmology, 15 laparoscopic bariatric surgery, 16 thyroid surgery 17 and stomatology surgery. 18 Patients undergoing gynecological laparoscopic surgery are at high risk for PONV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Previous studies have shown that the mechanism of penehyclidine reducing the incidence of PONV is complex, which may be related to its blocking of the muscarinic acetylcholine receptor, which is involved in the development of PONV through various mechanisms. Recent clinical studies have shown that penehyclidine for prevention of PONV has made good progress in some surgical procedures, such as ophthalmology, 15 laparoscopic bariatric surgery, 16 thyroid surgery 17 and stomatology surgery. 18 Patients undergoing gynecological laparoscopic surgery are at high risk for PONV.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, Ding et al found that penehyclidine (bolus 5mg, IV) did not reduce the incidence and severity of postoperative PONV in bariatric surgery patients. 16 In a study of patients undergoing gynecological laparoscopic surgery, Zhang et al observed that a single dose of penehyclidine before anesthesia also did not reduce the incidence of PONV. 27 Some of the above studies are based on a single dose of intravenous penehyclidine to investigate the prevention of PONV.…”
mentioning
confidence: 99%
“…The combination of serotonin antagonists with dexamethasone is a common dual therapy used to prevent PONV for high-risk patients undergoing various surgical procedures, such as laparoscopic bariatric surgery (palonosetron 0.25 mg plus dexamethasone 10 mg), laparoscopic cholecystectomy (palonosetron 0.075 mg plus dexamethasone 8 mg), and cesarean delivery (palonosetron 0.075 mg plus dexamethasone 4 mg). 10 11 12 13 14 Even with double prophylaxis, PONV may still occur frequently. 5 15 Searching for factors related to PONV in various clinical situations may contribute to better PONV control.…”
Section: Introductionmentioning
confidence: 99%